KONSEP EKONOMI BEROKAH DALAM TRADISI PENGAJIAN KOLOMAN MADURA DI DESA LARANGAN BADUNG KECAMATAN PALENGAAN PAMEKASAN - Sibyan, Hidayatus; Fawaid, Akh.; Zaini, Moh. (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2023)
This study aims to investigate the concept of Berokah Economics in the tradition of recitation in Madura. The focus of this research is to understand how the concept is applied in the economic practices of the people involved in recitation activities in Madura. The research method used is qualitative research with a descriptive approach. Data was collected through participatory observation, in-depth interviews, and analysis of documents related to recitation traditions and related economic practices. The research participants consisted of members of the Madurese community involved in recitation activities and economic practices. The results of the study show that the concept of Berokah Economics in the tradition of recitation in Madura has significant implications for empowering the community's economy. Study participants integrate the teachings of the Islamic religion in their daily economic practices. They apply principles such as sincerity, piety to Allah, and gratitude in doing business. This concept influences the way they conduct transactions, interact with consumers, and manage their economic resources. also serves as a forum for friendship and exchange of information between members of the study.